2023
DOI: 10.1111/jopr.13663
|View full text |Cite
|
Sign up to set email alerts
|

Effect of immersion in disinfectants on the color stability of denture base resins and artificial teeth obtained by 3D printing

Abstract: PurposeTo evaluate the effect of immersion in disinfecting solutions on the color stability of denture base resins and artificial teeth obtained by 3D printing.Materials and methodsForty discs (15 × 3 mm) were obtained for each group: Lucitone 550 and Cosmos Denture 3D (denture base resins), Duralay and Cosmos TEMP 3D (artificial teeth resins). The discs were immersed in disinfectant solutions: Corega Tabs, 2% chlorhexidine digluconate, 0.25% sodium hypochlorite, and distilled water. Color measurements were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…The results indicated that the protocol using immersion in sodium hypochlorite at 0.25% generated a significant color change of the resins after the simulation of 1, 3, and 5 years. This result corroborates the literature [2,20]. The change in the optical characteristics of the resins can occur due to the dissociation of chloride ions, which are extremely reactive and may cause surface changes and stains, which is a disadvantage of this solution [2].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results indicated that the protocol using immersion in sodium hypochlorite at 0.25% generated a significant color change of the resins after the simulation of 1, 3, and 5 years. This result corroborates the literature [2,20]. The change in the optical characteristics of the resins can occur due to the dissociation of chloride ions, which are extremely reactive and may cause surface changes and stains, which is a disadvantage of this solution [2].…”
Section: Discussionsupporting
confidence: 90%
“…Although the results are promising concerning mechanical and surface properties compared to conventional resins, further long-term follow-up studies are required [3,16]. In addition, some studies have evaluated the effects of chemical disinfectants on biofilm control [2,20,21] and the properties of 3D-printed resin. These studies are important because biofilm control is essential for maintaining oral health.…”
Section: Introductionmentioning
confidence: 99%
“…However, we emphasize that recently published data showed that the immersion in SH 0.25%, CD 2%, and AP for the simulated period of 6 months significantly changed the color of the COS 3D-printed resin. 43 …”
Section: Discussionmentioning
confidence: 99%
“…LU specimens (control group) were obtained by the conventional pack-press technique. Metal matrices with cavities with the disc dimensions were included in denture flasks, arranged between glass sheets [ 32 ]. The LU acrylic resin was manipulated in the manufacturer’s powder/liquid ratio and inserted into the cavities for pressing.…”
Section: Methodsmentioning
confidence: 99%